TFP growth in old and new Europe - Michael C. Burda; Battista Severgnini (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
Using Solow-Törnqvist residuals as well as two alternative measurements, we present estimates of total factor productivity (TFP) growth in a sample of 30 European economies for the period 1994-2005. In most of Western Europe, we find a deceleration of TFP growth since 2000. However, the economies of New Europe exhibit a higher level of TFP growth overall and have slowed less than those of Old Europe. In the new market economies of Central and Eastern Europe, we find both high TFP growth as well as acceleration in the second half of the sample. Regression evidence from Western Europe suggests that product market regulation may adversely affect TFP growth and may thus impair convergence.
Keywords: D24; O47; P27; 330; Total factor productivity growth; Solow residual; product and labor market regulation; Produktivität; Wirtschaftswachstum; Regulierung; Vergleich; Schätzung; Westeuropa; Osteuropa; Europa